Antigens of Corynebacterium pseudotuberculosis with promising potential for caseous lymphadenitis vaccine development: a literature review (Caderno de Ciências Agrárias, 2016)
The caseous lymphadenitis (CL) is an infectious disease of chronic evolution that affects sheep and goats, causing great economic losses in goat and sheep production. CL is caused by Corynebacterium pseudotuberculosis. Diagnosis is based on the isolation and identification of the agent and may be carried out serologically ELISA. Vaccination of the flock can be an important tool in preventing CL. The search for new antigens can generate vaccines that are more effective in disease control. Thus, the purpose of this article is to summarize the state of the art on the main antigens of Corynebacterium pseudotuberculosis with good potential for caseous lymphadenitis vaccine development. Various types of vaccines are commercially available and are based on live attenuated and/or inactivated microorganisms, microorganism extracts and/or recombinant proteins or subunits. In addition to the available forms are in the experimental stage DNA-based vaccines, and those using live recombinant microorganisms. We can realize that several studies have been conducted to find antigens for vaccine formulations that can ensure a good immune response to vaccinated animals. Some studies have reported promising antigens and others have shown that there is a need to search for new antigens for CL vaccine production more efficient. Although several studies have already been made in an attempt to develop an effective vaccine against the CL, there is a vast field to be searched and many antigens can still be discovered and studied to give a CL vaccine that is effective, inexpensive and practical.